“Хүн” ойлголт өвөрмөц хэллэгт илрэх нь: Understanding idioms & idiomatic expressions describing people - B., Enkhsaruul (Mongolian Journal of Foreign Languages and Cultures, 2023)
In this paper, written in the spirit of anthropological linguistics paradigm of anthropocentrism is used as a principle of research "in the language of man ', and more specifically man in phraseology. Idioms, being a special and indivisible part of a language, are the crystallization of anthropology. With the development of globalization, idioms play an increasingly important role in spreading national culture. Due to its special and close relationship with culture, idioms are very difficult to learn. In view of the difficulty in and significance of idiom learning, due attention and efforts should be given to the cultural comparison and contrast between Mongolian, Russian and English idioms. By introducing the knowledge of idioms, the article analyzes idioms as a topic to be studied in anthropology. It starts with an introduction which includes basic knowledge of idioms. Meanwhile, many examples are cited to illustrate.